Enzymatic debridement in critically injured burn patients — Our experience in the intensive care setting and during burn resuscitation. Issue 4 (June 2022) - Bowers, C.; Randawa, A.; Sloan, B.; Anwar, U.; Phipps, A.; Muthayya, P.
Highlights: We present an established protocol for the use of enzymatic debridement in resuscitation level burn injury. Enzymatic debridement offers unique benefits in resuscitation level burn injury. Enzymatic debridement in resuscitation level burn injury must be treated as surgical procedure. Abstract: Background: Much of the recent literature on bromelain based enzymatic debridement of burn injury has focused on its use in smaller burn injury and specialist areas such as the hands or genitals (Krieger et al., 2012; Schulz et al., 2017a, b, c, d). This is despite the original papers describing its use in larger burn injury (Rosenberg et al., 2004, 2014). The current EMA license for Nexobrid™ advises that it should not be used for burn injuries of more than 15% TBSA and should be used with caution in patients with pulmonary burn trauma and suspected pulmonary burn trauma. The original safety and efficacy trial of NexoBrid™ limited its use to 15% TBSA aliquots with concern regarding the effect of bromelain on coagulation. In a European consensus paper of experienced burns clinicians, now on its second iteration, 100% of respondents agreed that "up to 30% BSA can be treated by enzymatic debridement based on individual decision" (Hirche et al., 2017). Hofmaenner et al.'s recent study on the safety of enzymatic debridement in extensive burns larger than 15% provides some further evidence that "bromelain based enzymatic debridement can be carried out safely in large-area burns" (Hofmaenner et al., 2020) but the literature is scant in these larger debridement areas. In our centre we have been using enzymatic debridement for resuscitation level burn injury since 2016. We have gained significant learning in this time; this article aims to describe our current protocol for enzymatic debridement in this patient population and highlight specific learning points that might aid other centres in using enzymatic debridement for larger burn injury. Method: We performed a search of the IBID database to identify all adult patients who satisfied the inclusion criteria of resuscitation level burn injury (defined as total burn surface area (TBSA) ≥15% in patients aged >16 years), or level 3 admission following burn injury and who underwent Enzymatic Debridement. A case note review was completed, and details comprising patient demographics, TBSA, mechanism of burn, presence of inhalation injury, sequencing of debridement, length of ICU and hospital stay, blood product utilisation and the need for autografting were recorded. No ethical approval has been sought for this retrospective review. Results: We identified 29 patients satisfying the inclusion criteria (Table 1). Between June 2016 and June 2020 the average total burn size of patients who had at least some of their burn treated by enzymatic debridement increased from 21.4% in 2016/17 to 34.7% in 2019/20. In these patients the actual area treated by enzymatic debridement also increased from 11.9% TBSA to 20.3% TBSA. 19 patients (66%) had enzymatic debridement performed within 24 h of injury, a further 2 patients (7%) within 48 h after injury. Patients were more likely to have enzymatic debridement commenced in the first 24 h after injury if they had circumferential limb injury (39% vs 9%) or were planned for enzyme only debridement (78% vs 28%). Those who were planned for combination enzyme and surgical debridement were more likely to have enzymatic debridement commenced after the first 48 h (75%). We have performed enzymatic debridement overnight on one occasion, for a patient who presented with circumferential limb injury and was determined to undergo urgent debridement. Conclusion: Much of the literature has described the use of enzymatic debridement in smaller burns, and specialist areas. However, it is our opinion that the advantages of enzymatic debridement appear to be greater in larger burns with a facility for whole burn excision on the day of admission in the ICU cubicle. We have demonstrated significantly reduced blood loss, improved dermal preservation, reduced need for autografting, and a reduction in the number of trips to theatre. We would advocate that both the team and the patient need to be as prepared as they would be for a traditional surgical excision. The early part of our learning curve for enzymatic debridement in resuscitation level injuries was steep, and we were able to build on experience from managing smaller injuries. We recommend any team wishing to using enzymatic debridement gain experience in the same way and develop robust local pathways prior to attempting use in larger burn injuries.